Avifauna de uma área de cerrado do leste de Mato Grosso – Brasil : composição, riqueza e abundância de aves e a complexidade da vegetação - Castilho, Lorena da Silva (2013)
Bird species richness in the Cerrado is the third of Brazil (837 species) and second in number of endemics (30 species). This biome is considered one of the world's biodiversity hotspots. However, many areas in Cerrado have not had their birds sampled adequately yet. This study aimed to characterize the bird community of Serra Azul State Park in Barra do Garças, eastern Mato Grosso. We analyzed the species richness and composition of bird communities, including the presence of migrant species, endemic, rare, endangered and bioindicators of high environmental quality. The study also aimed to assess the pattern of preference for forest habitats of species and trophic guilds occupied. The avifauna of part of Pé da Serra Azul Environmental Protection Area (APA) and of Serra Azul State Park (PESA) was studied from 2007 to 2012. Birds records were made by direct observation or contacts and hearing by the capture recapture with mist nets and banding. We recorded 257 bird species belonging to 23 orders and 50 families and Tyrannidae family was predominant in number of species (35). Among the recorded species are included regional migrants (19), seasonal migrant in the northern hemisphere (four); a seasonal migrant in the southern hemisphere; endemic species (8); four near-threatened with extinction (Rhea americana, Lophornis gouldii, Charitospiza eucosma and Suiriri islerorum,) and some remarkable records for the region (Geranoaetus albicaudatus, Spizaetus melanoleucus, Pseudastur albicollis, Elanoides forficatus, Ibycter americanus, Asio flammeus and Coccycua minuta). Almost half of the birds recorded was dependent partial forest (43.5%) and belonged to the insectivorous guild trophic (44%). The birds sampled in PESA is rich in number of species, including endemic, rare and almost endangered. Besides, maintain migrant species. These data reinforce the importance of this area to dwelling and maintain this community of birds. Thus, the PESA can be considered an important area of Cerrado in this region, providing local shelter, breeding and feeding of birds to the community site.